Do Caloric Test Results Affect the Prognosis of Sudden Hearing Loss? - Süha Beton; Muharrem Gerçeker (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim: The aim of this study is to evaluate the prognostic value of caloric test results in patients with sudden hearing loss.Material -Method: We evaluated 23 patients with sudden hearing loss who were hospitalized. Age, sex, etiology, accompanying pathologies and prognostic factors were examined. Temporal Magnetic Resonance Imaging (MRI) was used to exclude all patients with acoustic neurinoma. Audiological assessment of the patients were performed before and after treatment and also caloric tests were performed to all of the patients.Results: The mean age of patients were 41.2±12.01 and the mean covering of disease was found to be 9 days. According to the pure-tone audiograms of the patients at administration to our clinic with sudden sensorineural hearing loss, 8 patients (34.8%) had mild sensorineural hearing loss, 2 (8.7%) had moderate sensorineural hearing loss, 5 (21.7%) had severe sensorineural hearing loss and 8 (34.8%) had profound sensorineural hearing loss. According to the configurations of the audiogram, 4 cases (17.4%) had up-sloping type, 1 (4.3%) had down-sloping type, 10 (60.9%) had flat type, and 8 (34.8%) had total hearing loss. Type 14 patients (60.9%) had tinnitus, and 6(26.1%) had vertigo. The treatment protocol included different combinations of bed rest, salt restriction, steroids, plasma expander dextrans and urografin administration. Complete recovery was achieved in 48.3 % of the patients. Four patients (17.4%) had positive caloric test pathology. These patients also had vertigo. Three of these patients had perfect hearing recovery after treatment.Conclusion: We found no significant difference between groups of those with a positive caloric test and negative caloric test.